Postural limb abnormality: an unusual presentation of retroperitoneal Schwannoma - Anand, Gautam; Sharma, Deborshi; Meena, Sanjay; Ahuja, Arvind; Chauhan, Devendra Singh (International Surgery Journal, 2022)
Schwannoma is a tumor of soft tissue originating from Schwann cells that rarely appears in the retroperitoneum. Presentation depends on the site of disease leading to mostly pressure symptoms, sometimes with distal manifestations. Because of its complex location, it has varied presentations and is always a diagnostic dilemma. We reported a rare case of retroperitoneal schwannoma having mild difficulty in walking due to flexion deformity of left hip joint as the only initial presenting symptoms. Following imaging studies, a retroperitoneal mass was found. Partial excision of the tumor was performed, with the histology finding consistent with the retroperitoneal schwannoma. Patient was followed up for the last 2 years and had no evidence of recurrence.